Hot‐Spot Engineering Through Soft Actuators for Surface‐Enhanced Raman Spectroscopy (SERS) Applications. Issue 16 (18th May 2021) - Liman, Gorkem; Yildiz, Emrecan; Ilhan, Hasan; Cetin, Arif E.; Demirel, Gokhan
Abstract: Surface‐enhanced Raman spectroscopy (SERS) is a powerful analytical tool to detect molecular species at ultralow concentrations. However, considering current approaches, controlling and tuning plasmonic hot‐spot formations where the Raman signal enhancements maximize are still challenging due to high process cost, complexity, and inability of large‐area fabrication. To address these problems, a strategy is demonstrated based on the controlled folding of polymeric materials, which is a new perspective in the field of SERS. Manipulation of hot‐spot formations through controlled polymer folding enables a Raman signal enhancement up to 70 folds for the probe methylene blue molecule. Furthermore, sample collection and analysis have been successfully implemented through the magnetic field control of the platform motion and folding manipulation. The results demonstrate that soft actuator platforms can bring new modalities in sensing applications. Abstract : The discovery of effective "hot‐spot engineering" approaches is of great interest not only to widen surface‐enhanced Raman spectroscopy (SERS) applications but to further elucidate fundamental questions. Here, polymer‐based soft actuators are fabricated for the manipulation of hot‐spot formations. Remarkable SERS enhancements are achieved by controlling the polymer folding, indicating the great promise of soft actuator systems as next‐generation SERS platforms.